The Olive Oil Monophenolic Secoiridoid Ligstroside Aglycone Suppresses Melanoma Progression by Targeting the BRAF Signaling Pathway - Md Ashiq Mahmud; Abu Bakar Siddique; Afsana Tajmim; Judy Ann King; Khalid A. El Sayed (Molecules)
Melanoma is among the most abundant malignancies in the US and worldwide. Ligstroside aglycone (LA) is a rare extra-virgin olive oil-derived monophenolic secoiridoid with diverse bioactivities. LA dose–response screening at the NCI 60 cancer cells panel identified the high sensitivity of the Malme-3M cell line, which harbors a BRAF V600E mutation. Daily oral 10 mg/kg LA exhibited potent in vivo antitumor effects against Malme-3M cells xenograft in a nude mouse model by targeting the BRAF signaling pathway. A human Clariom S microarray analysis of the collected Malme- 3M tumors identified 571 dysregulated genes, with the downregulation of pathways critical for melanoma cells growth and survival. A Western blot analysis of the collected animal tumors further validated the downregulation of the mutated BRAF–MAPK axis, as well as the GPD1 and ELOVL6 expression levels. A histopathological analysis of Malme-3M tumor sections showed extensive focal tumor necrosis in treated mice. An immunofluorescence study of tumor sections showed notable reductions in proliferation marker ki67 and the vasculogenesis marker CD31 in treated tumors. These findings promote LA as a potential nutraceutical lead for the control of the BRAF V600E mutant melanoma.